The SEE-IT Trial: emergency medical services Streaming Enabled Evaluation In Trauma: study protocol for an interventional feasibility randomised controlled trial - Scott Munro; Janet Holah; Heather Gage; Richard Lyon; Cath Taylor; Jill Maben; Julia Williams; Mark Cropley; Simon S Skene; Carin Magnusson; Kate Bennett-Eastley; Craig Mortimer; et al. (BMJ Open, 2023)
Introduction Accurate and timely dispatch of emergency medical services (EMS) is vital due to limited resources and patients’ risk of mortality and morbidity increasing with time. Currently, most UK emergency operations centres (EOCs) rely on audio calls and accurate descriptions of the incident and patients’ injuries from lay 999 callers. If dispatchers in the EOCs could see the scene via live video streaming from the caller’s smartphone, this may enhance their decision making and enable quicker and more accurate dispatch of EMS. The main aim of this feasibility randomised controlled trial (RCT) is to assess the feasibility of conducting a definitive RCT to assess the clinical and cost effectiveness of using live streaming to improve targeting of EMS.Methods and analysis The SEE-IT Trial is a feasibility RCT with a nested process evaluation. The study also has two observational substudies: (1) in an EOC that routinely uses live streaming to assess the acceptability and feasibility of live streaming in a diverse inner-city population and (2) in an EOC that does not currently use live streaming to act as a comparator site regarding the psychological well-being of EOC staff using versus not using live streaming.Ethics and dissemination The study was approved by the Health Research Authority on 23 March 2022 (ref: 21/LO/0912), which included NHS Confidentiality Advisory Group approval received on 22 March 2022 (ref: 22/CAG/0003). This manuscript refers to V.0.8 of the protocol (7 November 2022). The trial is registered with the ISRCTN (ISRCTN11449333). The first participant was recruited on 18 June 2022.The main output of this feasibility trial will be the knowledge gained to help inform the development of a large multicentre RCT to evaluate the clinical and cost effectiveness of the use of live streaming to aid EMS dispatch for trauma incidents.Trial registration number ISRCTN11449333.